Analisis Faktor yang Mempengaruhi Kinerja Keuangan UMKM Tahun 2023: Studi Kasus pada Pelaku UMKM di Kecamatan Banjarsari, Kota Surakarta - Riska Febriyanti; Susilaningtyas B.Kurniawati; Syahriar Abdullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the influence of : (1) Capital, (2) Human Resources, (3) Partnership on the financial performance of MSMEs in Banjarsari District, Surakarta City. The method used in this study is a quantitative method with data analysis techniques using multiple linear regression. This study used probability sampling method, which is a simple random sampling technique. The sample of this study was 100 respondents who were MSME actors in Banjarsari District who were randomly invited. This study used primary data obtained through questionnaires that had been taken directly with Likert scale. The results of this study in T and F tests show that the variables of capital, human resources and partnerships affect the financial performance of MSMEs. The results of the R2 coefficient test have an Ajusted R Square value of 44.6% and the remaining 55.4% is influenced by variables outside this study.